Evaluation of various specialty protein sources as replacements for spray-dried animal plasma in diets for segregated early-weaned pigs - Nessmith, W.B.Jr.; Bergstrom, J.R.; Loughmiller, J.A.; Smith, J.W., II; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
We used high-health status, weanling pigs to evaluate six different protein sources as replacements for spray-dried animal plasma. Spray-dried blood meal, spray-dried egg, spray-dried wheat gluten, extruded soy protein concentrate, select menhaden fish meal, and soybean meal each replaced 2.5 or 5.0% spray-dried animal plasma. Pigs fed increasing levels of spray-dried blood meal, spray-dried egg, or soybean meal had decreased ADFI; however, increasing levels of select menhaden fish meal, extruded soy protein concentrate, and spray-dried wheat gluten had no influence or increased ADFI. For the high-health pigs used in this trial, select menhaden fish meal, extruded soy protein concentrate, and soybean meal appear to be effective in replacing a portion of the spray-dried plasma in the segregated-early weaned (SEW) diet. However, in contrast to other studies, the level of spray-dried animal plasma was not observed to have an effect on SEW pig performance. The conflicting results between this study and past trials in the performance of spray-dried blood meal and spray-dried egg indicate that quality standards should be established for all protein sources.
Keywords: Swine; Protein source; Weanling pigs